A NOVEL, HERBAL REMEDY FROM SIPHONOCHILUS AETHIOPICUS FOR THE TREATMENT OF ASTHMA - Horak, R. M.; Wadiwala, E.; Meoni, P.; Fouche, G.; van Rooyen, S.; Harding, N.; Maharaj, V. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Scientific research on traditional medicines can lead to new pharmaceutical products, typically herbal formulations or new chemical entities. The Bioprospecting group of CSIR Biosciences focuses on the scientific validation of traditional medicines leading to new therapeutically active ingredients to be developed as herbal medicines or prescription drugs. South Africa’s rich plant biodiversity is estimated to consist of approximately 24 000 indigenous plant species, representing about 10% of all higher plants on earth. CSIR’s bioprospecting scientists work with traditional healers to gather indigenous knowledge and through a collaboration programme, Siphonochilus aethiopicus (Schweinf.) B.L. Burtt, was identified for the treatment of asthma. Literature studies on this species mainly provided anecdotal information and little scientifically evaluated biological data for the treatment of asthma. Fractionation of the organic extract of the rhizomes led to the isolation of a major compound that was chemically characterized as a previously reported furanoterpenoid [1]. The structural assignment of the compound was based on a detailed study of the high field 1D and 2D NMR. Biological assaying of extracts of the plant and the furanoterpenoid showed effects in in vitro glucocorticoid receptor binding, 5-lipoxygenase, phosphodiesterase 4 and nuclear factor-κB assays pointing at a possible anti-inflammatory and bronchodilation effect of the plant material. The extract was also tested for inhibition of bronchoconstriction in rodent models possibly supporting the traditional use of the plant which has been chemically profiled and standardized using HPLC mass specrometry.Reference[1] Cedric W. Holzapfel, Ben-ErikVan Wyk, (2002), Phytochemistry, 59, 405–407